ANALYSIS OF IMPLEMENTATION DAYCARE BASED ON INTEGRATIVE HOLISTIC IN BANYUMAS REGENCY - Marini, Asri; Handayani, Sri Sularti Dewanti (BELIA: Early Childhood Education Papers, 2019)
The purpose for this research is to acknowledge the daycares that use integrative holistic in Banyumas Regency. Based on Lumbung Data Pokok Pendidikan Jawa Tengah 2018, there were 16 institut of daycares spread in 23 subdistricts. That mean that the amount of daycares in Banyumas is still lacking, and the quality is still unknown. That is why this research was made simply to acknowledge the quality of daycares with Integrative Holistic in Banyumas. This research took place in Banyumas with the head of the daycare as the subject. The method used is survey method. The researcher used the Saturation Sampling means that the entire daycares in Banyumas which included into the main educational data in Jawa Tengah used questionnaires and interviews as the submition method. Based on the questionnaire result and also several interviews, found out that 14 daycares are at the state of high criteria and 1 daycare is at the state of middle criteria. The average score from 14 daycares is 80,8% which is outomatically included into high criteria. Sekar Kemuning Daycare is included into meddle class because there are no structured teaching learning process, children?s development result, and no parenting with anyeducational institution. Meanwhile for the 14 daycares that are included into high criteria have been using Integrative Holistic apporoachment for their educational service, health care, nutrients and service, protection service, taking care service. The quality of the daycares that have been using Integratif Holistic approachment in Banyumas Regency could be seen from the serrices to the children. The relation between the daycare and the educational institution has become the main indicator. In acknowlegging the quality of daycares with Integrative Holistic approachment in Banyumas Regency. Other institution that are Puskesmas, dental clinic, Posyandu, Himpaudi, and also educational department. Aside from the institution partnership above, it also cooperated with dance academy, police department, public figure, citizenship department, psychologist, baby spa, Du?afa wallet, and Society?s Self-supporting Institution.